Burundi : Sixth Review Under the Extended Credit Facility Arrangement, and Request for Extension and Augmentation of Access. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Burundi's Sixth Review Under the Extended Credit Facility (ECF) arrangement and Request for Extension and Augmentation of Access. The macroeconomic outlook is broadly favorable, driven by continued public investment and a gradual recovery in agriculture; however, external vulnerabilities persist owing to a protracted decline in coffee exports and high volatility of coffee prices. The IMF staff supports the completion of the sixth review under the ECF and the authorities' requests for an augmentation of access and extension of the current ECF arrangement through March 2016, which will be instrumental to catalyze donor support needed to address Burundi's protracted balance-of-payments problem.